Religous and Political Role of Javanese Ulama in Johor, Malaysia - Arik Dwijayanto; Yusmicha Ulya Afif (Journal of Islamic Studies and Humanities, 2019)
The migration of Javanese Muslim community to Malaysia in the past was not only dominated by groups of workers such as labours and miners but also from religious Muslim groups (¬ulama). Javanese ulama as Muslim religious scholars formed an integral part of Muslim communities in Malaysia. Their role as religious leaders often means that they are consulted in all areas of Muslim life, including the realms of politics, social affairs and economics. However, there was sufficient appreciation of their role in Muslim society in various scholastic works. It is also only in recent years that interest has been shown in the study of Javanese ulama in Malaysia. This article argues that for most of Malaysia’s history, Javanese ulama have been largely apolitical and it was only in the 20th century that they attempted to carve a larger religious space for themselves in an attempt to assert their authority and influence. It briefly highlights the historical relationship between Javanese ulama and various government authorities in Malaysia focuses on their religious and political influence in relation to the role they played and the contribution they made, and shows how the Javanese ulama have tried to involve in the religious and political role in Johor, Malaysia. In order to contribute to the existing studies, this article aims to explore the impact of migration and religious contribution of Javanese Ulama in Johor, Malaysia.